Automation of the Creation of the Schedule at the University: Mathematical Model - KHABIPOV, R.I. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The work aims to describe a mathematical model of the automation of the scheduling process in an educational institution. Also, the approaches to the compilation of the optimal schedule are considered. In the studied tasks, a large amount of initial original information is used, which differs in its composition, and contains a large number of requirements that must be taken into account. Therefore, scheduling refers to the class of NP-complete integer programming problems, which implies that as the number of values of given variables increases, the complexity of the solution will grow exponentially. RESUMEN El objetivo del trabajo es describir un modelo matemático de la automatización del proceso de programación en una institución educativa. También se consideran los enfoques para la compilación del horario óptimo. En las tareas estudiadas se utiliza una gran cantidad de información original inicial, que difiere en su composición, y contiene una gran cantidad de requisitos que deben tenerse en cuenta. Por lo tanto, la programación se refiere a la clase de problemas de programación de enteros NP-completos, lo que implica que a medida que aumenta el número de valores de variables dadas, la complejidad de la solución crecerá exponencialmente.